Manajemen Strategi Pembelajaran dengan Sistem Boarding School dalam Upaya Menumbuhkan Kemandirian dan Kepedulian Siswa di Era 4.0: Studi Kualitatif di SMP Insan Terpadu Boarding school Paiton Probolinggo Jawa Timur - Muhammad Zaenal Arifin; Faisal Mas’udi (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
To realize education that produces a generation that has a strong personality, educational institutions must be urged to innovate, not only related to the curriculum and management tools, but also operational and methodological strategies and technical. This is necessary given the existence of educational institutions currently faced with various complex challenges. Educational institutions are now facing a swift flow of change due to globalization that has led to competition in the management of educational institutions, both public and private. On the other hand the rapid development of technology faced with the industrial revolution 4.0. this has implications for the world of education where the demand for quality human resources is one thing that must be considered. To deal with the era of education 4.0 education is needed that can form a generation that is creative, innovative, and competitive. SMP Insan Terpadu Paiton implement learning that fosters independence and care seems to have been pursued in a variety of learning environments, especially in preparing students for the 4.0 era with 21st century learning both at school and in the hostel. Efforts to foster independence and concern for students in schools, implemented with the role of technology in some aspects of school management systems and also in the overall interaction of learning in the form of integration of subjects and extracurricular activities, while in the hostel is realized in the form of student settings that are integrated with the application an online system in the management of several existing dormitories and also in the form of exemplary caregivers of the hostel, warm dialogue that is full of meaning, training for independence and care, as well as a celebration or appreciation `of each value of kindness that students do.